Korespondencja Alfreda Tarskiego z Heinrichem Scholzem w latach 1938–1946 - Besler, Gabriela; Książek, Kacper; Stokłosa, Sebastian; Tkaczyk, Adam (Filozofia Nauki, 2024)
Both Alfred Tarski (1901–1983) and Heinrich Scholz (1884–1956) were prominent figures in the field of mathematical logic. They exchanged letters at least between 1938 and 1953, as evidenced by correspondence preserved in the Nachlass Scholz collection (Universitäts- und Landesbibliothek Münster, Germany). Only excerpts from three of Tarski’s letters to Scholz have been published so far. The aim of the paper is to present the content of the previously unpublished correspondence from the years 1938 to 1946. The letters discuss such topics as academic cooperation, publication prospects, future research plans, ongoing studies, organization of the scholarly community, academic travels, didactic activities, exchange of papers, information about mutual friends, and Scholz’s health problems.